2018
DOI: 10.3389/fnbeh.2018.00069
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor and Neurocognitive Dysfunctions Parallel Early Telencephalic Neuropathology in Fucosidosis Mice

Abstract: Fucosidosis is a lysosomal storage disorder (LSD) caused by lysosomal α-L-fucosidase deficiency. Insufficient α-L-fucosidase activity triggers accumulation of undegraded, fucosylated glycoproteins and glycolipids in various tissues. The human phenotype is heterogeneous, but progressive motor and cognitive impairments represent the most characteristic symptoms. Recently, Fuca1-deficient mice were generated by gene targeting techniques, constituting a novel animal model for human fucosidosis. These mice display … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…We next examined if loss of FUCA1 was associated with changes in tissue architecture. Consistent with previous studies on fucosidosis ( 19 , 20 ), histological analysis revealed prominent cytoplasmic vacuolation in a variety of tissues with marked effects in neurons and glia in the central nervous system, hepatocytes in the liver, acinar cells in the pancreas, and the kidney ( Fig. 1 E ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We next examined if loss of FUCA1 was associated with changes in tissue architecture. Consistent with previous studies on fucosidosis ( 19 , 20 ), histological analysis revealed prominent cytoplasmic vacuolation in a variety of tissues with marked effects in neurons and glia in the central nervous system, hepatocytes in the liver, acinar cells in the pancreas, and the kidney ( Fig. 1 E ).…”
Section: Resultssupporting
confidence: 91%
“…Although the principal aim of our study was to understand the importance of glycan breakdown in macroautophagy, our study also yields significant insights regarding the etiology of fucosidosis. Behavioral characterization of Fuca1 −/− mice revealed deficiencies in motor function and reduced exploration over time (habituation), characteristics consistent with a neurodegenerative phenotype as seen in fucosidosis patients and in a previous mouse model of the disease ( 20 ). Importantly we show, as has been reported for other lysosomal storage disorders, that the accumulation of lysosomal material in fucosidosis can be attributed to a defect in macroautophagy ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 54%
“…The authors demonstrated behavioral alterations in Fuca1-deficient mice that coincided with early signs of neuropathology (at 3 months of age); subtle abnormalities in sensorimotor and cognitive abilities were identified. The animals displayed lysosomal dysregulation (increased Lamp1 expression) and evidence of neuroinflammation and secondary storage of GM2 ganglioside, as early manifestations of brain pathology [ 85 ]. These abnormalities preceded neuron loss but imply an early stage of neuropathology encompassing an extended endosomal-lysosomal network, secondary lipid storage, and emerging microgliosis and astrogliosis [ 86 ].…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…Because these defects were observed during developmental stages, they support a mechanism of hypomyelination rather than demyelination ( Fletcher et al, 2011 ; 2014). In addition, a Fuca1 knockout mouse exhibited lysosomal dysregulation, lipid accumulation, neuroinflammation, and behavioral deficits (e.g., impaired coordination and spatial learning) that parallel the motor and intellectual deficits observed in fucosidosis patients ( Stroobants et al, 2018 ). Thus, both canine and murine disease models indicate that many downstream effects of FUCA1 deficiency contribute to myelin defects in fucosidosis.…”
Section: Lysosomal Lipid Metabolism and Catabolism Defectsmentioning
confidence: 99%